Influenza vaccination for immunocompromised patients: summary of a systematic review and meta‐analysis. (27th August 2013) - Beck, Charles R; McKenzie, Bruce C; Hashim, Ahmed B; Harris, Rebecca C; Zanuzdana, Arina; Agboado, Gabriel; Orton, Elizabeth; Béchard‐Evans, Laura; Morgan, Gemma; Stevenson, Charlotte; Weston, Rachel; Mukaigawara, Mitsuru; et al.
Abstract : Vaccination of immunocompromised patients is recommended in many national guidelines to protect against severe or complicated influenza infection. However, due to uncertainties over the evidence base, implementation is frequently patchy and dependent on individual clinical discretion. We conducted a systematic review and meta‐analysis to assess the evidence for influenza vaccination in this patient group. Healthcare databases and grey literature were searched and screened for eligibility. Data extraction and assessments of risk of bias were undertaken in duplicate, and results were synthesised narratively and using meta‐analysis where possible. Our data show that whilst the serological response following vaccination of immunocompromised patients is less vigorous than in healthy controls, clinical protection is still meaningful, with only mild variation in adverse events between aetiological groups. Although we encountered significant clinical and statistical heterogeneity in many of our meta‐analyses, we advocate that immunocompromised patients should be targeted for influenza vaccination.